Strategi Guru dalam Membentuk Karakter Disiplin pada Siswa MAN 1 Kerinci - Sappaile, Baso Intang; Sujarot, Sujarot; Handayani, Eka Selvi; Amarullah, Ahmad; Prastawa, Singgih; Haddar, Gamar Al (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2023)
This research is expected to be able to examine the procedures carried out by educators in forming the disciplinary personality of students at MAN 1 Kerinci. The character of discipline is an important aspect of student self-awareness, which affects academic achievement and everyday life. The exploratory strategy used is subjective with a contextual investigative approach. Information was gathered through class perceptions, interviews with instructors, and examination of related records. Examination participants consist of educators related to outstanding students at MAN 1 Kerinci. The results of the study show that educators use different techniques in shaping the personality of discipline in students. This system combines set rules and standards, implementation of clear results, organized and planned learning, and a model of regulation by educators. Educators also involve students in making choices regarding class rules to increase students' sense of pride and obligation to discipline. This study provides an understanding of the procedures that can be carried out in forming the personality of discipline in students at MAN 1 Kerinci. The consequences of this exam are expected to be a reference for educators, schools, and other related parties in making successful people training programs.